2011
DOI: 10.1007/s00421-011-2126-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic fitness on oxygen uptake kinetics in heavy intensity swimming

Abstract: This study aimed to characterise both the VO2 kinetics within constant heavy-intensity swimming exercise, and to assess the relationships between VO2 kinetics and other parameters of aerobic fitness, in well-trained swimmers. On separate days, 21 male swimmers completed: (1) an incremental swimming test to determine their maximal oxygen uptake (VO2 max), first ventilatory threshold (VT), and the velocity associated with VO2max (vVO(2 max)) and (2) two square-wave transitions from rest to heavy-intensity exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 63 publications
8
43
1
5
Order By: Relevance
“…Sousa et al (2011a) also studied the VO 2 off-kinetics in the same intensity, reporting an asymmetry between the on-and off kinetic limits, although both periods were best characterized by a single exponential regression model. Also Reis et al (2011) characterized VO 2 kinetics, but in the heavy intensity domain, reporting that a faster VO 2 kinetics allowed higher aerobic power outputs, and that the slow component is lower in swimmers with higher ventilatory thresholds.…”
Section: Vo 2 Kineticsmentioning
confidence: 99%
“…Sousa et al (2011a) also studied the VO 2 off-kinetics in the same intensity, reporting an asymmetry between the on-and off kinetic limits, although both periods were best characterized by a single exponential regression model. Also Reis et al (2011) characterized VO 2 kinetics, but in the heavy intensity domain, reporting that a faster VO 2 kinetics allowed higher aerobic power outputs, and that the slow component is lower in swimmers with higher ventilatory thresholds.…”
Section: Vo 2 Kineticsmentioning
confidence: 99%
“…During such training, NIRS offers the potential to report upon peripheral measurements of muscle oxygenation that are indicative of adaptive local responses to training. 33 In conjunction with this, it has been suggested that a local measurement of muscle oxygenation during swim exercise would contribute to a multimodality approach that is perhaps warranted to enable a more detailed evaluation of swim athletes, 13 and complement the global measurements of oxygen consumption that are already attainable. Furthermore, this technology can be applied to other open water sports such as rowing, canoeing, and windsurfing.…”
Section: Comparing Differences In Swim Technique In Athletes and Triamentioning
confidence: 99%
“…It has been suggested that when combined with global measures of oxygen consumption a multimodality approach of local and systemic physiological monitoring may provide valuable information that could help to more accurately identify athlete response to workload and also inform exercise prescription. 13,14 However, little to no research has focused upon the peripheral aerobic parameters associated with swim exercise, and no research has focused upon muscle oxygenation status in or out of the water.…”
Section: Introductionmentioning
confidence: 99%
“…O componente lento (CL) é característico dos domínios pesado e severo do exercício 4,5 , e tem sido analisado na corrida 6 , ciclismo 7 , e natação 8 . Basicamente, o CL é caracterizado por uma resposta exponencial do VO 2 sobreposta à resposta primária, com amplitude que pode variar entre 250 e 600 mLO 2 .min -1 , aproximadamente, sendo sua quantificação realizada de forma pontual (início pré-definido), ou por meio de modelagem matemá-tica (em esforços limitados a 6 -10 minutos de exercício).…”
Section: Introductionunclassified
“…Entre os mecanismos fisiológicos que são sugeridos para explicar este custo adicional do VO 2 , apesar de algumas controvérsias e informações não conclusivas, estão o acúmulo de metabó-litos e de catecolaminas, o trabalho dos músculos ventilatórios e cardíaco, a elevação da temperatura corporal, a ativação de músculos assessórios e o recrutamento de fibras do tipo II, que são menos eficientes 4,13 . Tem sido sugerido na literatura que o CL representa uma redução da eficiência muscular e que pode estar associado com a tolerância ao exercí-cio 8 . Portanto, a análise dos principais fatores que podem estar associados ao CL, como também as implicações do CL para a prática do exercício físico podem auxiliar na prescrição do treinamento aeróbio em indivíduos sedentários, ativos e treinados 11,[14][15][16][17] , tanto para a melhora da performance quanto para a melhora do estado de saúde e qualidade de vida.…”
Section: Introductionunclassified